Development of a dynamic model for piezoelectric raindrop energy harvesting - Wong, Voon-Kean (2018)
Over the last decade, advancement of microelectronics has triggered a growing interest in ambient energy harvesting. Ambient energy can be found in various forms such as: thermoelectric, acoustic, solar, and mechanical vibrations. Most of the stated ambient energy sources have been thoroughly investigated. One of the relatively unexplored ambient energy sources is raindrop impact energy. Raindrop impact energy harvesting is achieved by converting the strain induced by an impinging raindrop on a piezoelectric beam into usable electrical energy. Most of the conducted research from the literature only considered single droplet impact on a piezoelectric beam. More interestingly, actual field test has yet to be conducted. These are the areas that the research will cover.